Kyrgyz Students' Acceptance of QR Code Use in Organic Chemistry Course - Chinara Jumabaeva; Gülgün Afacan Adanır; Kulumkan Sartova; Gulshat Muhametjanova (Universidad de Málaga, 2024)
Science disciplines require a deeper study of theoretical material by performing laboratory work, which includes performing experiments. In this regard, it will be useful to actively introduce new technologies into the educational process. In this study, QR codes were integrated into the Organic Chemistry Course textbook to direct university and high school students to the appropriate videos about the experiments. In this respect, this study aimed to analyze university and high school students` acceptance of the QR code technology used in the "Organic Chemistry" course. This research model is based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology2 (UTAUT2). Hence, the study included perceived playfulness, social influence, facilitating conditions, hedonic motivation, perceived ease of use, perceived usefulness, behavioral intention, and attitude as the major antecedents of students' acceptance of QR codes. In total, 204 Kyrgyz students in university and high school level participated in this study. Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis was applied to analyze the effects of factors on students' acceptance of QR codes. The study revealed that facilitating conditions, hedonic motivation, social influence, perceived ease of use, and perceived usefulness are the significant factors towards students` acceptance of QR code use in Organic Chemistry course.